Manipulation of autophagy in cancer cells: an innovative strategy to fight drug resistance. (June 2013) - Aredia, Francesca; Scovassi, A Ivana
Autophagy is a catabolic process activated by stress conditions and nutrient deprivation, to which it reacts by promoting the degradation of damaged organelles and misfolded/aggregated proteins, as well as generating new energetic pools. Paradoxically, in cancer cells, which signal the dangerous microenvironment occurring during clinical therapies, autophagy could promote their proliferation and sustain drug resistance. Special attention is given to autophagy manipulation in order to counteract drug resistance of cancer cells. This article describes the basic properties of autophagy and focuses on the strategies of manipulating it.